Effect of Laser Cleaning on EH36 Steel Surface Quality in Maritime Industry Applications - Tourunen, Eter; Väisänen, Inka; Iizuka, Olivia; Peuronen, Anssi; Kamboj, Nikhil; Piili, Heidi; Salminen, Antti (United Kingdom, 2026)
This study examines the effect of laser cleaning on EH36 steel plates coated with epoxy paints. These materials are used in maritime applications, such as in shipbuilding. Paint layers were removed by using a laser beam generated by an IPG 100W pulsed nanosecond fiber laser with a wavelength of 1064 nm. The laser cleaning parameters included a pulse width of 25 ns, frequency of 100 kHz, and scanning speed of 450 mm/s. The tests were carried out using a laser power of 25 W, applying four or eight treatment cycles. Surface inspection was performed using a Bruker Alicona Infinite Focus G6 and a Malverna Panalytical Aeris X-ray diffractometer (XRD), along with visual evaluation. Results showed complete removal of paint layers, confirmed by visual inspection and XRD, with no damage to the base metal. Surface roughness values remained within acceptable limits for maritime industry standards. The mechanism of paint removal was identified as ablation, allowing layer -by-layer removal. This suggests that laser -cleaned surfaces can be directly repainted, avoiding time-consuming re -sandblasting. The study highlights the industrial importance of laser cleaning for efficient paint removal and maintenance in maritime applications.
20th Nordic Laser Materials Processing Conference